Mixed feelings and vexed passions : exploring emotions in biblical literature - Spencer, F. Scott (Franklin Scott) (Atlanta : SBL Press, 2017)
"This ground-breaking collection of essays explores the rich array of emotions in biblical literature displayed by divine and human figures. How do biblical characters' "feelings" affect their relationship with God, one another, and the world? How do they mix together, for good or ill, for flourishing or vexation? Deeply engaged with both ancient and modern contexts, including the burgeoning interdisciplinary study of emotion in the humanities and sciences, an international team of Hebrew Bible and New Testament scholars offers incisive case studies of "passions" ranging from joy, happiness, and trust to grief, hate, and disgust"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Added to collection customer.56279.3 - Master record variable field(s) change: 072
Keywords: Bible -- Criticism, interpretation, etc; Bible; Emotions -- Biblical teaching; Emotions -- Biblical teaching; BIBLES / General; RELIGION / Biblical Reference / General; RELIGION / Biblical Reference / Handbooks; Criticism, interpretation, etc; Electronic books